Tourism Entropy as a Critical Factor for Destination Sustainability: Assessment of Carrying Capacity Through IoTs and Determination of Tourism Satisfaction - Theocharous, Antonis L.; Avdimiotis, Spyridon; Karakitsios, Apostolos (My University, 2019)
This paper introduces a novel methodology to address the issue of destination carrying capacity assessment and monitoring, while, to develop a new tool to enable effective and optimized policy making in tourism sector. Tourism fits together a chain value, where stakeholders are working as cogwheels targeting the sustainability. An inherent requirement towards the objectives of sustainability is the capacity of policy makers to sustain the available social, economic, and environmental resources. Given the facts that (i) carrying capacity is a complex, dynamic, multidimensional concept, apparently vague, as such it is quite difficult to assess and monitor and (ii) each destination has unique characteristics, varying the extent and intensity of tourism development, the research proposal refines and implements measures and establishes a state-of-the-art data collection network in order to monitor tourism development in terms of sustainability and to establish an integrated carrying capacity estimation framework. Since validity and reliability of input data is a critical issue, different kind of sensors for environmental data (IoTs) are used, as well as web mining methods and field surveys, statistical information and secondary research results. Also, specialized analysis methods are applied and integration of all sources is achieved, defining the characteristics of the tourism destination ecosystem from the perspective of entropy change, in order to provide planning, policy making, and decision support, as well as a set of intelligent tools.
Keywords: carrying capacity; smart tourism; tourism entropy; sustainability; tourism satisfaction; environment protection; policy making; tourism destination; innovation; IoTs